FUZZY - COGNITIVE APPROACH IN PROBLEMS OF PROCESS CONTROL MEMBRANE DISTILLATION OF CONTACT - Ладієва, Л. Р; Момотенко, Д. О. (Science-based technologies, 2016)
The paper presents the cognitive model of the process contact membrane distillation. Currently, many countries are experiencing an acute shortage of fresh water, due to the intensive development of industry and agriculture, which led to a sharp increase in water consumption and increasing pollution. The introduction of membrane technologies is accompanied by a number of issues to be addressed, namely cost and lifetime of the membrane equipment. The proposed fuzzy cognitive map, KMD, which takes into account external and internal parameters that influence the course of the process. Also in the proposed model takes into account the preparatory stage component of Cost of raw materials and of contact membrane distillation. An conceptual matrix of relationships cognitive model KMD.